International crime and justice - Natarajan, Mangai (Cambridge ; New York : Cambridge University Press, 2011)
"International crime and justice is an emerging field that covers international and transnational crimes that have not been the focus of mainstream criminology or criminal justice. This book examines the field from a global perspective. It provides an introduction to the nature of international and transnational crimes and the theoretical perspectives that assist in understanding the relationship between social change and the waxing and waning of the crime opportunities resulting from globalization, migration, and culture conflicts. Written by a team of world experts, it examines the central role of victim rights in the development of legal frameworks for the prevention and control of transnational and international crimes. It also discusses the challenges to delivering justice and obtaining international cooperation in efforts to deter, detect, and respond to these crimes. This book is arranged in nine parts covering the subject matter of international criminal justice. Each of the short chapters provides readers with an understanding of the main concepts relevant to the topic and sensitizes them to the complex nature of the problems"--
Keywords: Transnational crime; Criminology; Criminal justice, Administration of; Criminal justice, Administration of